Pengаruh Komunіkаsі Аsertіf Dаn Pengаwаsаn Melekаt Terhаdаp Kіnerjа Kаryаwаn PT. Restu Tаnjung Permаі - Adam Samsudin Noor; Aep Saefullah; Ahmad Fadli; Ramadani Pardian; Zubair Arza (BADAN PENERBIT STIEPARI PRESS, 2021)
As one of the largest coal mining service companies in Indonesia, PT. RTP is engaged in integrated mining equipment rental services with international standards for mining companies in Tabalong. The purpose of this study is to find out the effect of assertive communication (X1) on the performance of PT. RTP (Y), to find out the effect of attached supervision (X2) on the performance of PT. RTP (Y), and to find out the effect of assertive communication (X1) and inherent supervision (X2) together on the performance of PT. RTP (Y). The research method used in this research is quantitative analysis method. The data collection method used in this research is using a questionnaire. The results of this study are Assertive Communication has no significant effect on the performance of employees of PT. RTP. This is evidenced by the statistical results of the t test for the physical evidence variable because the value of tcount < ttable where -0.809 < 2.447 and the significance value obtained is 0.450 greater than the value of = 0.05. Inherent supervision has a significant effect on employee performance at PT. RTP. This is evidenced by the statistical results of the t test for the physical evidence variable with a value of tcount > ttable where 3.702 > 2.447 and the significance value obtained is 0.010 which is smaller than the value of = 0.05. Assertive communication and inherent supervision together have a significant impact on employee performance of PT. RTP. This is evidenced by the Fcount statistic of 8.030 which is greater than Ftable 4.76, it can be concluded that the independent variable of assertive communication (X₁), attached supervision (X₂) simultaneously has a significant effect on the dependent variable of employee performance (Y).